Analysis of geometric structure of woven fabrics surface. - Gabriela Kosiuk; Małgorzata Matusiak (Communications in Development and Assembling of Textile Products)
The geometric structure of the surface of textile materials is of significant functional, operational and aesthetic importance. The basic parameters of the woven fabrics’ structure are the following: weave, warp and weft density as well as warp and weft linear density. Roughness is one of the surface quality features most often assessed by quantitative indicators called surface roughness parameters. The aim of the presented research was to analyze the parameters characterizing the geometric structure of the surface of cotton woven fabrics with different weaves. Surface topography measurements were performed using the MicroSpy® Profile profilometer by FRT the art of metrology™. Using the Mark III software cooperating with the profilometer, a number of indices characterizing the geometric structure of the fabric surface and histograms illustrating the frequency of occurrence of points of a certain height on the tested surface were determined. The research confirmed that, on the basis of the results obtained with the profilometer, it is possible to analyze comprehensively the topography of the fabric surface.